Selective Methods to Investigate Authenticity and Geographical Origin of Mediterranean Food Products. Issue 6 (18th August 2021) - Krajnc, Bor; Bontempo, Luana; Luis Araus, Jose; Giovanetti, Manuela; Alegria, Carla; Lauteri, Marco; Augusti, Angela; Atti, Naziha; Smeti, Samir; Taous, Fouad; Amenzou, Nour Eddine; Podgornik, Maja; et al.
ABSTRACT: The Mediterranean diet is promoted as one of the healthiest and closely linked to socioecological practices, knowledge and traditions, promoting sustainable food production, and linking geographical origin with food quality and ecosystem services. Consumer adherence to this dietary pattern drives increased consumption of authentic "premium" foods, such as Iberian pig meat and dry-cured ham from Portugal and Spain, argan oil from Morocco, " Djebel " lamb from Tunisia and truffles from Italy and Slovenia, i.e., food products that respond to current ethical, environmental and socially sustainable demands. Geographical indication and appellation of origin can increase traditional food products competitiveness, but the high-value recognition of these products can also lead to economically motivated product adulteration. It is therefore imperative to protect the high added value of these unique food products by ensuring their quality, authenticity, provenance and sustainable production systems. In this review, we provide a critical evaluation of the analytical methods that are currently used for the determination of provenance and authenticity of these Mediterranean products as well as possible strategies for improving the throughput and affordability of the methods discussed.